2015
DOI: 10.1159/000430204
|View full text |Cite
|
Sign up to set email alerts
|

Eruberin A, a Natural Flavanol Glycoside, Exerts Anti-Fibrotic Action on Pancreatic Stellate Cells

Abstract: Background: Eruberin A (2, 3-dehydroflavonoid), a flavanol glycoside isolated from Pronephrium penangianum, has been used as a blood-nourishing folk medicine for centuries; however, it indeed possesses a variety of other health-promoting benefits including anti-fibrotic bioactivity. Activation of pancreatic stellate cells (PSCs) is the key initiating step in pancreatic fibrosis, which is a characteristic feature associated with chronic pancreatitis and pancreatic adenocarcinoma. Methods: The anti-fibrotic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Natural products have been shown to provide beneficial effects on various pathological conditions as we reported in previous studies (Tsang and Bian, ; Tsang et al , ). To this end, the pharmacological properties of natural compounds are of our particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…Natural products have been shown to provide beneficial effects on various pathological conditions as we reported in previous studies (Tsang and Bian, ; Tsang et al , ). To this end, the pharmacological properties of natural compounds are of our particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…NF-B has been shown to mediate high fat diet-related pancreatic fibrosis in rats [32]. Furthermore, inhibition of NF-B expression by Eruberin A (2, 3-dehydroflavonoid), a flavanol glycoside isolated from Pronephrium penangianum, has been reported to suppress the expression of fibrotic mediators including -SMA, fibronectin, and type 1-collagen in pancreatic stellate cells [33]. Activation of pancreatic stellate cells is the key commencing step in pancreatic fibrosis, which is a characteristic feature associated with CP.…”
Section: Discussionmentioning
confidence: 99%
“…In LTC‐14 cells, a cell line retained characteristics and morphological features of PSCs (primary pancreatic stellate cell), eruberin A ( 18 ) can not only effectively inhibit the expression levels of α ‐smooth muscle actin, fibronectin and type I‐collagen (20 μg/ml) as well as the stimulation of post transforming growth factor‐ β in sonic hedgehog signaling pathway (5 ng/ml), but also notably decrease the activation of NF‐κB and the phosphorylation of PI3 K (phosphoinositide 3‐kinase)/Akt (serine‐threonine kinase), which demonstrated that it significantly suppressed the expression levels of fibrotic mediators in PSCs and its anti‐fibrotic mechanism was considered to associate with an attenuation of PI3 K/Akt/NF‐κB signaling way …”
Section: Pharmacologymentioning
confidence: 99%